Co- and Pre-Seismic Crustal Deformations Related to Large Earthquakes Between Years of 2009 and 2023 UsingContinuous CORS-TR GNSS Observationsin the Anatolian Diagonal (Turkey) - Dokukin Petr Aleksandrovich; Guvenaltin Muhammed Ali; Kaftan Vladimir; Toker Mustafa (Russian Journal of Earth Sciences)
Synoptic animations of internal displacements and deformations of the earth’s crust were obtained based on the results of continuous GNSS observations in Eastern Anatolia from 2009 to 2023. The spatiotemporal patterns of the seismic deformation process in connection with the tectonics of the region have been identified. It is shown that dilatation and total shear strains evolve in concert with the migration of the strongest earthquakes Elazig, Elazig-Malatya and devastate Karamanmaraş series. Two years before the occurrence of the devastating earthquakes of 2023, a deficit of internal displacements of GNSS stations developed in the area of their epicenters. The conducted research suggests that the strongest events of 2009-2023 are connected by a unitary seismic deformation process. The most important action in this case is the SW movement of the Anatolian block as monolithic element. In the development of movements and deformations, a flow of increasing stresses is observed in the direction from Karliova Triple Junction to the SW to the area of the strongest seismic events on February 2023. It originates east of the Karliova Triple Junction where the Arabian Plate encounters an obstacle. The role of mantle flows in the seismic process is assessed.